Application of Information Motivation Behavior Skill on Tertiary Preventive Behavior of Type 2 Diabetes Mellitus Patients at Blora Health Center - Jihan Nabilla; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Health Promotion and Behavior, 2025)
Background: Diabetes mellitus (DM) is a priority disease that not only requires control efforts but is also important for prevention efforts. Complications that occur in type II DM patients can be prevented with tertiary preventive behavior. This tertiary preventive behavior can be done by applying the Information Motivation Behavior (IMB) skill model. The purpose of this study is to explore the influence of the application based on the IMB model on tertiary prevention behavior in type II DM patients. Subjects and Method: This study is cross sectional from April-May 2024. The sample used was 200 type 2 DM patients aged >18 years and selected by random sampling technique at the Blora Health Center, Central Java. The dependent variable was the tertiary preventive behavior of type 2 DM patients. The independent variables were information, motivation and behavioral skills. Data collection using questionnaires and data analysis using path analysis with Stata 13. Results: Tertiary preventive behavior of patients with type 2 diabetes mellitus was directly influenced by behavioral skills (b= 5.80; CI 95%= 4.73 to 6.87; p <0.001), information (b= 1.25; CI 95%= 0.01 to 2.50; p= 0.047) and gender (b= -1.60; CI 95%= -0.60 to -2.59; p= 0.002). Tertiary preventive behavior of type 2 DM patients through behavioral skills is indirectly influenced by information, motivation, age and education. Information is indirectly influenced by motivation and education. There was no significant effect on gender on behavioral skills. Conclusion: Tertiary preventive behavior is directly influenced by behavioral skills, information and gender. Tertiary preventive behavior is indirectly influenced by information, motivation, age, and education through behavioral skills. Tertiary preventive behavior is indirectly influenced by gender and education through information.